KINERJA PEGAWAI DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN PADA KANTOR KECAMATAN SUNGAI PANDAN KABUPATEN HULU SUNGAI UTARA - H. Zainal Arifin (Al-KALAM : JURNAL KOMUNIKASI, BISNIS DAN MANAJEMEN, 2014)
The central issue in this study is less optimal public service to the community, such as care of the ID card, family card and others. This study aims to: ( 1 ) To find evidence of direct services provided in the Pandan River District Employee Population Administration Services to the community, ( 2 ) To determine the reliability of the Pandan River District Employee Population Administration Services to the community, ( 3 ) To determine the Employee Responsiveness River District of North Hulu Sungai Pandan .The method used in this study were A study to provide a detailed overview of the background, the nature, characteristics, typical of the performance pegawai kecamatan in pelayanan publik. Collecting data with interview techniques, observation and documentation. Analysis of the research results are used qualitative analysis with data reduction step , the presentation of the data and draw conclusions .The results showed : ( 1 ) direct evidence of service in the Office have not been able to support the improvement of service quality as the number of service personnel are still lacking, especially his ability is not supported by the availability of technical equipment and adequate service -based technology, the information service and the conditions of service of less comfortable, ( 2 ) Reliability has not been able to support the quality of service, because they can not fulfill the exact period of time, which is often the timeliness of customer complaints, although in terms of the accuracy of product services and product destruction service level is good enough, ( 3 ) Responsiveness layananbelum support quality of care because officials are still not ready sepenuhhati, can not respond well to the needs of customers as well as less serious response to the problems faced. Keywords:  Performance, Services Quality, Administration.